Analysis of the diversity and function of the microbiota in infected root canals of type 2 diabetes mellitus with apical periodontitis - Li, Yuzhi; Wu, Song; Zhang, Yong; Zhang, Ting; Hu, Can; Zhang, Peng; Yang, Wanrong; Xiong, Sheng; Liu, Yanni (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeThis study aimed to compare the compositional differences and functions of microbial communities in infected root canals of teeth with apical periodontitis (AP) and/or type 2 diabetes mellitus (T2DM) using 16S rDNA sequencing.MethodsEighteen participants were categorized into two groups based on their health conditions: AP and AP complicated with T2DM (APDM). Infected root canal microbiota was clinically collected for 16S rDNA sequencing. Subsequent statistical and bioinformatics analyses were conducted after sequencing by NovaSeq, encompassing diversity analysis, intergroup difference analysis, and functional prediction analysis.ResultsThe core microbiome of root canal microorganisms was similar in the two groups, which mainly consisted of Bacteroidota, Firmicutes, Synergistota, Actinobacteriota, Proteobacteria, Fusobacteriota, Spirochaetota. The root canals of the affected teeth of APDM had significantly higher abundance of Olsenella_uli, Peptostreptococcaceae_bacterium _oral_taxon_113_str_W5053, W5053, Pyramidobacter_piscolen, Pyramidobacte, Synergistaceae, Synergistales was significantly higher than AP group (P<0.05). Under the condition of T2DM, root canal microbial metabolism was predominantly enriched towards functions of the phosphotransferase system, ABC system, amino acid metabolism, and carbohydrate metabolism.ConclusionThe microbial community in the infected root canals of APDM showed similarities to AP yet exhibited differences in certain species and microbial functions.